Clinic-based Case-control Study of the Association between Body Mass Index and Endometrial Cancer in Puerto Rican Women - Charneco, Eileen; Ortiz, Ana P.; Venegas-Rios, Heidi L.; Romaguera, Josefina; Umpierre, Sharee (Puerto Rico Health Sciences Journal, 2010)
Background: Obesity is an established risk factor for endometrial cancer (EC). This association, however, has not been studied in Puerto Rico, where overweight and obesity have reached epidemic levels (38% and 26%, respectively). Methods: A hospital based case-control study was designed to evaluate the association between body mass index (BMI) and EC in women older than 21 years of age. Seventy-four prevalent EC cases diagnosed between January 2004 and August 2007 and a random sample of 88 healthy controls were recruited from gynecology clinics of the Medical Sciences Campus, University of Puerto Rico. Demographic, reproductive, lifestyle, and clinical information was obtained via structured telephone interviews and medical chart review. Unconditional logistic regression models were used to estimate adjusted odds ratios (OR) and 95% confidence intervals (CI). Results: A significant trend was observed between BMI and EC in bivariate analyses (p < 0.05). Results showed that overweight (25.0 > BMI < 29.9 kg/m2) (OR=4.4, 95% CI=1.6-12.3) and obese (BMI ≥ 30 kg/m2) (OR=9.9, 95% CI=3.6-26.9) women were more likely to have EC when compared to non-obese women. In multivariate analysis, obese women had a 4-fold greater possibility of EC (OR=4.1; 95% CI: 1.8-8.6) than nonobese women, after adjusting for age, education, employment status, hypertension and diabetes diagnosis, use of oral contraceptives and consumption of poultry. Conclusion: Consistent with previous studies worldwide, adult obesity was a strong predictor for EC in this sample of Puerto Rican women. Thus, cancer control strategies should promote weight reduction strategies to reduce disease risk in this population.